Directional coupler design for orbital angular momentum mode-based photonic integrated circuits - Lee, In Joon; Kim, Sangin (Optics Express, 2020)
An orbital angular momentum (OAM) dividable on-chip directional coupler design is proposed. To guide OAM modes of topological charge number l = ±1, a waveguide needs to support TE01 and TE10 modes with degeneracy. When a directional coupler is made with such an OAM mode waveguide, it is additionally required to equalize the horizontal-direction coupling strengths of those two OAM constitutive eigenmodes. Base on the coupled mode theory formulation, we have found that this requirement can hardly be satisfied and devised a modified cross-shaped waveguide structure to solve this problem. An example design of OAM mode directional coupler is demonstrated. The coupling length of the designed device is 670 μm, and our numerical simulation showed negligible degradation of OAM mode purity during the operation of complete optical power transfer between two waveguides. To the best of our knowledge, this is the first proposal of the on-chip OAM mode directional coupler. The proposed design approach can be applied to implement various devices for OAM mode-based photonic integrated circuits.
Keywords: Coupled mode theory; Coupling length; Coupling strengths; Design approaches; Orbital angular momentum; Photonic integrated circuits; Topological charges; Waveguide structure